Hypoxia regulates endogenous double-stranded RNA production via reduced mitochondrial DNA transcription - Arnaiz, E; Miar, A; Dias Junior, AG; Prasad, N; Schulze, U; Waithe, D; Nathan, JA; Rehwinkel, J; Harris, AL (Frontiers, 2021)
Hypoxia is a common phenomenon in solid tumours strongly linked to the hallmarks of cancer. Hypoxia promotes local immunosuppression and downregulates type I interferon (IFN) expression and signalling, which contribute to the success of many cancer therapies. Double-stranded RNA (dsRNA), transiently generated during mitochondrial transcription, endogenously activates the type I IFN pathway. We report the effects of hypoxia on the generation of mitochondrial dsRNA (mtdsRNA) in breast cancer. We found a significant decrease in dsRNA production in different cell lines under hypoxia. This effect was HIF1α/2α-independent. mtdsRNA was responsible for induction of type I IFN and significantly decreased after hypoxia. Mitochondrially encoded gene expression was downregulated and mtdsRNA bound by the dsRNA-specific J2 antibody was decreased during hypoxia. These findings reveal a new mechanism of hypoxia-induced immunosuppression that could be targeted by hypoxia-activated therapies.